Studi Deskriptif Penerapan Pembuatan Karya Kreatif Scrapbook Pada Pembelajaran Seni Budaya Dan Keterampilan Kelas V SD Unggulan Aisyiyah Rejang Lebong - Dhinda Dhiandita Kurnia; Hasnawati Hasnawati; Wurdjinem Wurdjinem (Universitas Bengkulu, 2018)
This study aimed to describe the process of making and the creativeScrapbook masterpiece of 5th grade students SD Unggulan AisyiyahRejang Lebong on SBK Subject. The type of this research is a qualitativetype with descriptive method and participants observation technique. Thesubject of this research is 5thA students of SD Unggulan Aisyiyah RejangLebong. The research instrument is human instrument, by usingobsevation guidelines and interview guidelines. The results of the researchwere (1) The process of making four creative works of Scrapbook beginswith a discussion determining the theme to be selected in making thework. Followed by ornaments that support the theme. Next, create theornaments with drawing patterns on origami paper, cut the patternsthat have been made and coloring the ornaments using color paint.Then the ornament is affixed to the background paper. (2) Four creativeworks of Scrapbook made by students have contained elements andprinciples of fine arts. Among them, in the creative work of Scrapbook hasincluded elements of lines, colors, shades, textures, space and dark lighton Scrapbook ornaments. Placement of the ornaments on paper that hasmet the principles of art, unity, tone, full and harmony.